Análise crítica do discurso produzido por autores de universidades de países lusófonos sobre a internacionalização do campo do currículo no âmbito dos colóquios sobre questões curriculares. - Regis, Herman Wagner de Freitas (2021)
The object of the present research was the Critical Discourse Analysis (ACD) based on the theoretical assumptions of Norman Fairclough, proponent of the ACD Three-Dimensional Model, which was expanded in this thesis through the intersection of faircloughian categories with theoretical precepts of Universal Pragmatics, by Habermas (HABERMAS, 1984, 1987a, 1990a), with Bakhtin's conception via Julia Kristeva of intertextuality (KRISTEVA, 1986a, 1986b), with the assumptions of the Bakhtin Circle (BAKHTIN, 2011, 2016; VOLÓCHINOV, 2017), with Antonio Gramsci's notions about hegemony and power (GRAMSCI, 1978a, 1978b, 1978c) and with John Thompson's thought about ideology (THOMPSON, 1984, 2011). The objective we propose was to analyze the ideological effects produced by the speeches of the researchers from universities in Portuguese-speaking countries (Angola, Brazil, Cape Verde, Mozambique and Portugal) who discussed issues inherent to the internationalization of the curriculum field in two corpus, one of which consists of clippings of selected articles from the Annals of the XII Colloquium on Curricular Issues / VIII Luso-Brazilian Colloquium of Curriculum / II Luso-Afro-Brazilian Colloquium on Curriculum Issues and another one of texts, in various media, by authors who were part of the Scientific Committee of that event or who were part of its direction or organization. The hypothesis was that events are events based on structures, developed and organized as a reflection of the control of international organizations that maintain the asymmetry of power in the first world countries over economically disadvantaged countries. The analyzes were carried out using the Extended Three-Dimensional Model and answered that this hypothesis is confirmed by showing that international organizations such as the IMF, BM, OECD and others force a pro-internationalization discourse without respecting the diversity of each country, interested in verifying the damage on the countries outside the power blocs arising from this condition of subordination and manipulation. The analyzes corroborated to propose an Ideal Speech Situation (HABERMAS, 1990) as a communicative action to reduce the asymmetry of power in the public and private spheres in national and international curricular policies in the sense of social transformation in emerging, underdeveloped and developing countries. development.